2007
DOI: 10.1007/bf03217459
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics performance and the role played by affective and background factors peter grootenboer and brian hemmings

Abstract: In this article, we report on a study examining those factors which contribute to the mathematics performance of a sample of children aged between 8 and 13 years. The study was designed specifically to consider the potency of a number of mathematical affective factors, as well as background characteristics (viz., gender, ethnicity, and socioeconomic status), on children's mathematics performance. Data were collected by surveying the children and drawing on performance ratings from their teachers. A correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 25 publications
3
61
0
3
Order By: Relevance
“…There are various models describing the relationships between beliefs, values, attitudes, and emotions or feelings (e.g., Grootenboer, 2008;Grootenboer & Hemmings, 2007). Attitudes are usually seen as more affective and less cognitive than beliefs or values.…”
Section: Person's Mathematical Disposition Related To Her or His Belimentioning
confidence: 99%
“…There are various models describing the relationships between beliefs, values, attitudes, and emotions or feelings (e.g., Grootenboer, 2008;Grootenboer & Hemmings, 2007). Attitudes are usually seen as more affective and less cognitive than beliefs or values.…”
Section: Person's Mathematical Disposition Related To Her or His Belimentioning
confidence: 99%
“…Authors such as Onwuegbuzie and Wilson (2003), Ainley (2006) or Grootenboer and Hemmings (2007) have successfully demonstrated the importance of affective variables in the practices and hence in the definition of students' perceptions of mathematics.…”
Section: Introductionmentioning
confidence: 98%
“…There are numerous research in the literature concerning mathematics teaching and learning as well as mathematics performance especially so in the recent years considering the importance of the subject across the globe (Swetz, Langgulung & Johar, 1983;Alkhateeb, 2001;McGraw, Lubienski & Strutchens, 2006;Ramirez, 2006;Grootenboer & Hemmings, 2007;Tella, 2007;House & Telese, 2008;Ismail & Awang, 2008). These studies found many factors affecting mathematics learning and performance ranging from students' background, attitudes and motivation, teachers as well as school characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…These studies found many factors affecting mathematics learning and performance ranging from students' background, attitudes and motivation, teachers as well as school characteristics. For example, Alkhateeb (2001), McGraw et al (2006), Grootenboer & Hemmings (2007) and Ismail & Awang (2008) examined the relationship between background factors of the students including gender, and mathematics achievement in United Arab Emirates, United States and Malaysia, respectively. While Tella (2007) and Wang (2007) investigated the impact of motivation and self-concept on mathematics, House & Telese (2008) and Ramirez (2006) did a comparative evaluation of the determining factors of mathematics of mathematics achievement across countries.…”
Section: Introductionmentioning
confidence: 99%